2023
DOI: 10.1007/s00167-023-07459-z
|View full text |Cite|
|
Sign up to set email alerts
|

Gender‐specific distribution of knee morphology according to CPAK and functional phenotype classification: analysis of 8739 osteoarthritic knees prior to total knee arthroplasty using artificial intelligence

Stephanie Huber,
Jennyfer A. Mitterer,
Sascha M. Vallant
et al.

Abstract: Purpose Osteoarthritis of the knee is commonly associated with malalignment of the lower limb. Recent classiications, as the Coronal Plane Alignment of the Knee (CPAK) and Functional Phenotype classiication, describe the bony knee morphology in addition to the overall limb alignment. Data on distribution of these classiications is not suicient in large populations. The aim of this study was to analyse the preoperative knee morphology with regard to the aforementioned classiications in long leg radiographs prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 77 publications
3
11
1
Order By: Relevance
“…In the present study, the MPTA was similar between the groups, and was comparable to mean values in large datasets 6 . MPTA was, however, different at baseline, with more valgus This article is protected by copyright.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, the MPTA was similar between the groups, and was comparable to mean values in large datasets 6 . MPTA was, however, different at baseline, with more valgus This article is protected by copyright.…”
Section: Discussionsupporting
confidence: 85%
“…Evolution in technology combined with a stagnant development of clinical outcomes 5 has led to the introduction of robotic assisted surgery (RAS) for TKA. With its precision, RAS complements the now clear body of evidence that there is significant variability in knee morphotypes in the population 6 .…”
Section: Introductionmentioning
confidence: 89%
“…Nonetheless, the aforementioned studies primarily focused on healthy individuals and arthritic patients undergoing TKA. Therefore, it is noteworthy that the prevalence of CPAK phenotype I, characterized by varus alignment and an apex distal JLO, was higher in the present study as compared to the previously mentioned studies [12, 14, 18, 19, 31, 36, 37]. This may potentially be attributed to the association between pre‐arthritic varus alignment, increased loading of the medial compartment of the knee, and consequently the higher risk of OA progression primarily affecting the anteromedial compartment of the knee [34, 35, 38].…”
Section: Discussioncontrasting
confidence: 51%
“…Previous reports have demonstrated a higher prevalence of varus alignment among males compared to females [5, 30, 32]. Moreover, a prior study, specifically evaluating the gender‐specific distribution of CPAK knee phenotypes in osteoarthritic knees, reported that CPAK phenotypes characterized by a varus alignment were more common in males, whereas phenotypes characterized by a neutral or valgus alignment were more frequently observed in females [14]. These findings are supported by the current study evaluating patients with identical anteromedial OA, demonstrating a statistically significant predominance of pre‐arthritic varus alignment among males, both prior to and following medial UKA.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel classification systems, including the functional knee phenotype classification [7], have been put forth to comprehensively describe the relation between the mechanical axis (i.e., limb phenotype) and femoral and tibial joint line orientation (i.e., knee phenotype) of the individual knee [7,9,10]. However, most of these studies included both lateral and medial compartment OA-affected knees, or healthy knees, and focused on guidelines and implications for total knee arthroplasty [7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%